A Human Pluripotent Stem Cell Model of Facioscapulohumeral Muscular Dystrophy-Affected Skeletal Muscles. (23rd May 2016) - Caron, Leslie; Kher, Devaki; Lee, Kian Leong; McKernan, Robert; Dumevska, Biljana; Hidalgo, Alejandro; Li, Jia; Yang, Henry; Main, Heather; Ferri, Giulia; Petek, Lisa M.; Poellinger, Lorenz; et al.
Abstract : This work describes a monolayer system to differentiate human pluripotent stem cells (hPSCs) into skeletal muscle cells (SkMCs) and demonstrates disease-specific phenotypes in SkMCs derived from hPSCs affected with facioscapulohumeral muscular dystrophy. This is the first human stem cell-based cellular model for a muscular dystrophy suitable for high-throughput screening and drug development. Abstract : : Facioscapulohumeral muscular dystrophy (FSHD) represents a major unmet clinical need arising from the progressive weakness and atrophy of skeletal muscles. The dearth of adequate experimental models has severely hampered our understanding of the disease. To date, no treatment is available for FSHD. Human embryonic stem cells (hESCs) potentially represent a renewable source of skeletal muscle cells (SkMCs) and provide an alternative to invasive patient biopsies. We developed a scalable monolayer system to differentiate hESCs into mature SkMCs within 26 days, without cell sorting or genetic manipulation. Here we show that SkMCs derived from FSHD1-affected hESC lines exclusively express the FSHD pathogenic marker double homeobox 4 and exhibit some of the defects reported in FSHD. FSHD1 myotubes are thinner when compared with unaffected and Becker muscular dystrophy myotubes, and differentially regulate genes involved in cell cycle control, oxidative stress response, and cell adhesion. This cellular model will be a powerful tool for studying FSHD and will ultimately assist in the development of effective treatments for muscular dystrophies. Significance : This work describes an efficient and highly scalable monolayer system to differentiate human pluripotent stem cells (hPSCs) into skeletal muscle cells (SkMCs) and demonstrates disease-specific phenotypes in SkMCs derived from both embryonic and induced hPSCs affected with facioscapulohumeral muscular dystrophy. This study represents the first human stem cell-based cellular model for a muscular dystrophy that is suitable for high-throughput screening and drug development.